Finite Element Analysis of Crack Growth in Pipelines - Žmindák, Milan; Meško, Jozef; Pelagić, Zoran; Zrak, Andrej (Manufacturing Technology Journal, 2014)
The paper presents a short crack theory together with the finite element method (FEM), which is used to model crack initiation during the operational phase of a pipeline. To simulate the crack, the virtual crack extension (VCE) method, implemented in the FE code, is used. This paper describes the modelling and simulation of a welded pipeline with initiated crack in the beginning. A FEM modelling procedure for analysing the stress intensity factors (SIF's) and J-integral for two practical problems is presented. For the first problem the commercial software ANSYS was used to calculate the crack parameters in a straight pipe with a radial crack. The second problem deals with an axial crack tip in the main pipe of a welded tubular Y-joint. For this problem numerical results for calculated crack parameters and contour integrals are presented. The parameters were calculated by commercial software ABAQUS. For J-integral evaluation, the region on the surface of the blunted notch should be used to define the crack front.
Keywords: FEM; XFEM; stress intensity factor; J-integral; pipelines